Influence of Irrigation, Fertilizer and Variety on Grain Growth of Barley (Hordeum vulgare L.) - Mollah, MSI; Paul, NK (Journal of Bio-Science, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> An experiment was conducted in the experimental field of Rajshahi University Campus (AEZ-11) to study the influence of soil moisture and NPK fertilizers on grain growth of four varieties of barley (Hordeum velgare L.). Spikelet number (SN), spike dry weight (SDW), grain number (GN), grain dry weight (GDW), spike relative growth rate (spike RGR) and grain relative growth rate (grain RGR) were observed highest in the highest level of irrigation (40 mm). The highest amount of fertilizer (120N 75P 45K) produced the highest SN, SDW, GN, GDW, spike RGR and grain RGR. BHL-3 produced the highest SN, BARI Barley -2 produced the highest spike RGR, BARI Barley -1 produced the highest grain RGR and BL-1 produced the highest SDW, GN, and GDW. Key words: Irrigation, soil moisture, fertilizers, barley, grain growth. Â doi: 10.3329/jbs.v15i0.2205 J. bio-sci. 15: 69-75, 2007